Social Philosophy and Policy (Cambridge)
Social Philosophy and Policy is an interdisciplinary journal with an emphasis on the philosophical underpinnings of enduring social policy debates. The issues are thematic in format, examining a specific area of concern with contributions from scholars in different disciplines, especially philosophy, economics, political science and law. While not primarily a journal of policy prescriptions, some articles in each issue will typically connect theory with practice.
Keywords: sociology